Compare the Need of Additional Uterotonic Drugs for the Control of Post-Partum Hemorrhage after Caesarean Section - Choudhury, Farhana Haque; Ahmed, Shahnaz; Sumi, Sufia khatun; Rahman, Silvia (Journal of Current and Advance Medical Research, 2024)
Background: Management of Post-Partum hemorrhage is very crucial among women after Caesarean Section. Objective: The purpose of the present study was to compare the need of additional uterotonic drugs for the control of post-partum hemorrhage among women after Caesarean Section. Methodology: This randomized controlled trial was conducted in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2015 to December 2015 for a period of six months. Pregnant women diagnosed on the standard criteria admitted in BSMMU, Dhaka, Bangladesh were selected as study population by consecutive type of sampling. Randomization was performed according to computer generated simple random sampling method. An Uterotonic was an agent used to induce contraction or greater tonicity of the uterus. Then the patients were monitored per operatively and post operatively. All the information was recorded in data collection sheet. Main outcome variables were estimated blood loss. Results: A total number of 96 pregnant women were recruited for this study of which 48 cases were enrolled in group I and the rest of 48 case were enrolled in group II. The mean age with SD of the group I and group II were 24.4±4.7 years and 24.7±3.7 years. Before administration of drug, 44(91.7%) patients had well contracted uterus in group I and 41(85.4%) in group II. At 30 minutes after caesarean section, 48(100.0%) patients had well contracted uterine tone in group I and 47(97.9%) in group II. At 12 and 24 hours after caesarean section, 48(100.0%) patients had well contracted uterine tone in group I and group II respectively. The difference was not statistically significant (p>0.05) between two groups. Four (8.3%) patients need additional utero tonic in group I and 7(14.6%) in group II. The difference was not statistically significant (p>0.05) between two groups. In primary PPH of the study patients, it was observed that 2(4.2%) patients had primary PPH in group I and 6(12.5%) in group II. The difference was not statistically significant (p>0.05) between two groups. Conclusion: In conclusion, additional uterotonic drugs are needed for the control of post-partum hemorrhage among women after Caesarean Section. Journal of Current and Advance Medical Research, July 2023;10(2):53-59